Hong Kong's business regulation in transition - Wu, Changqi; Cheng, Leonard K. (1997)
The transition of Hong Kong's main economic activities from manufacturing to services is accompanied by gradual changes in the regulatory regimes for monopolies. The local telecommunication services industry has been liberalized, deregulation of public transport is taking shape, and the schemes of control for electricity suppliers are candidates for reform. In this paper, we review the evolution of business regulation in Hong Kong, analyze the salient features of its scheme of control regulation and evaluate the impact of transition from regulation to competition. To provide a sharp contrast between the difficulties of the traditional approach to regulation and the benefits of introducing competition, we focus on the cases of electricity and telecommunications. The direction for future changes is also discussed.
Keywords: Economische ontwikkeling; Economische politiek; Politik; Wirtschaftsentwicklung; Wirtschaftspolitik; Deregulation -- China -- Hong Kong; Public utilities -- Government policy -- China -- Hong Kong